2016
DOI: 10.1177/0972150916645675
|View full text |Cite
|
Sign up to set email alerts
|

On Supply Chain Integration to Free Trade Zones: The Case of the United States of America

Abstract: The interdependence of resources in a global marketplace, the advancement of technology and rising national economic constraints have compelled companies to excel in their supply chain performance. To that end, Free Trade Zones (FTZs) may help supply chains improve their bottom line while generating economic development to their geographical regions. The shift of manufacturing to overseas and recent changes in global trends, regulations and procedures call for a renewed understanding of FTZs from the perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In the zones, multiple institutional incentives such as free movement of goods and people and preferential taxation are provided. Since the 1980s, countries such as the United States and Brazil have established FTZs, which are conductive to attract foreign direct investment (FDI), and greatly promote trade development [ 8 , 9 , 10 ]. The Chinese government has always been committed to deepening reform and opening wider to the outside world.…”
Section: Introductionmentioning
confidence: 99%
“…In the zones, multiple institutional incentives such as free movement of goods and people and preferential taxation are provided. Since the 1980s, countries such as the United States and Brazil have established FTZs, which are conductive to attract foreign direct investment (FDI), and greatly promote trade development [ 8 , 9 , 10 ]. The Chinese government has always been committed to deepening reform and opening wider to the outside world.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, as the reduction in transaction costs will drive down the prices of local products in the zone, it will also affect the welfare level of domestic producers (Hamiltion and Sevensson, 1982) [11]. However, the vast majority of scholars are positive about the spillover effects of PFTZs, such as Benton et al (2016) [12] and Mohebi and Mirshojaee (2019) [13], who found that the construction of PFTZs attracts foreign direct investment, promotes the optimization and upgrading of the trade structure and thus strengthens the economic and trade ties with major countries in the world. Currently, scholars have also extensively discussed the spillover effects of PFTZs from various aspects, such as regional innovation development, economic growth, industrial development and knowledge spillover.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SCs exist in virtually all industries; be it consumer packages goods, automotive, agri-food, healthcare, military, or services such as education and tourism. More so in the last few decades, because of increasing populations, changing demographics, depletion of natural resources, increasing social instabilities, international trade facilitations (e.g., Benton et al 2016), and containerization (ocean shipping), most SCs have been extended over the globe in an attempt to efficiently match supply and demand. That is, it has been very rare that a company in isolation is viable.…”
Section: Sustainability and Supply Chain Managementmentioning
confidence: 99%